At the Conjunction of Love and Money: Comment on Julie A. Nelson, Does Profit-Seeking Rule Out Love? Evidence (or Not) from Economics and Law - William W. Bratton (Washington University Journal of Law & Policy, 2011)
In this Essay, the author discusses a question that arises in Julie A. Nelson's preceding essay—specifically, why maximization dominates people's thinking on firms. Bratton says that academic paradigm displaced the Great Depression regulatory state, which took people to the other side of money and love. He mentions that the theories that justify the New Deal regulatory state helps people to understand and appreciate the descriptive accuracy between “and” rather than “or” as the conjunction.
Keywords: Law & behavioral economics; Economics -- Political aspects; Corporation law; Capital market; Stockholders